The entrepreneurship research challenge [electronic resource] - Davidsson, Per (Edward Elgar, 2008)
Entrepreneurship is an emerging, dynamic and, to a considerable extent, unpredictable phenomenon and challenging research subject. In this book, one of the most experienced empiricists in this field has collected some of his ideas on how improved conceptualization and research design can make this challenge more manageable.